SuperVeg : the joy and power of the 25 healthiest vegetables on the planet - Celia Brooks (Sydney : Murdoch Books, 2018)
A vegetarian cookbook celebrating 25 health-enhancing vegetable 'heroes'. SuperVeg celebrates the power and flavour of plants by shining the spotlight on 25 of the most health-giving vegetables on the planet. In this heartfelt homage, vegetable expert Celia Brooks explores the formidable nutritional benefits of each veg, providing a wealth of supporting information including selection, preparation and cooking techniques. Over 100 creative, health-enhancing, everyday vegetarian recipes cover simple flavour pairings through to more substantial offerings, and bring the joy of powerful nutrition, deliciousness and versatility to your home kitchen
Keywords: COOKING Specific Ingredients Vegetables; Vegetarian cooking; Food and Drink